2014
DOI: 10.1149/2.002404jss
|View full text |Cite
|
Sign up to set email alerts
|

Complete Elemental Analysis of Low-ka-SiC:H Thin Films by Transmission FTIR Spectroscopy

Abstract: Fourier transform infrared (FTIR) spectroscopy is a popular technique for qualitatively investigating the chemical bonding of low dielectric constant (low-k) materials utilized in nanoelectronic Cu interconnects. However, quantitative FTIR analysis of low-k materials with widely varying stoichiometry has proven challenging due to numerous optical interference effects, variations in IR absorption strength with optical constants, and a negligible IR activity for homopolar bonds. In this paper, these challenges a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…It was found that, to obtain the corrected spectra with M minimized, one needed to allow both inputs to be treated as free parameters. 16,20 However, the values for refractive index and thickness that were obtained from the procedure of minimizing M did not deviate too far (<1−5%) from the ellipsometric values, so these values do serve as a good starting point for the correction procedure.…”
Section: Fully Coherent Correction Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was found that, to obtain the corrected spectra with M minimized, one needed to allow both inputs to be treated as free parameters. 16,20 However, the values for refractive index and thickness that were obtained from the procedure of minimizing M did not deviate too far (<1−5%) from the ellipsometric values, so these values do serve as a good starting point for the correction procedure.…”
Section: Fully Coherent Correction Methodsmentioning
confidence: 99%
“…The first results from the superposition of numerous components of the IR beam that were multiply reflected at the film surface and filmsubstrate interface. 20 The frequency of these fringes varies with the film thickness and can range from 500-10,000 cm −1 depending on the thickness of the film. 21 Multiple reflections in the substrate generate the second source of interference fringes.…”
Section: Thin Film T-ftir Background Subtraction and Interference Fri...mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, low-dielectric-constant materials have been commonly employed in microwave devices, ultra-large-scale integrated circuits, and other applications (Sato et al, 2013;Hong et al, 2020). Many materials have been introduced to achieve lower dielectric constants, such as Al 2 O 3 (Su et al, 2014), SiCN (Zhou and Zhang 2015), BN (Hong et al, 2016), SiC (Milosevic and King 2014), and SiO 2 (Carta et al, 2014;Joseph et al, 2015). Although the resulting materials have excellent properties, they are expensive and limited in terms of output.…”
Section: Introductionmentioning
confidence: 99%